A Survey of Differential-Fed Microstrip Bandpass Filters: Recent Techniques and Challenges - Yasir I. A. Al-Yasir; Naser Ojaroudi Parchin; Ahmed M. Abdulkhaleq; Mustafa S. Bakr; Raed A. Abd-Alhameed (Sensors, 2020)
Differentially driven devices represent a highly promising research field for radio frequency (RF), microwave (MW), and millimeter-wave (mmWave) designers and engineers. Designs employing differential signals are essential elements in low-noise fourth-generation (4G) and fifth-generation (5G) communications. Apart from the conventional planar MW components, differential–fed balanced microstrip filters, as promising alternatives, have several advantages, including high common-mode rejection, low unwanted radiation levels, high noise immunity, and wideband harmonic suppression. In this paper, a comprehensive and in-depth review of the existing research on differential-fed microstrip filter designs are presented and discussed with a focus on recent advances in this research and the challenges facing the researchers. A comparison between different design techniques is presented and discussed in detail to provide the researchers with the advantages and disadvantages of each technique that could be of interest to a specific application. Challenges and future developments of balanced microstrip bandpass filters (BPFs) are also presented in this paper. Balanced filters surveyed include recent single-, dual-, tri-, and wide-band BPFs, which employ different design techniques and accomplish different performances for current and future wireless applications.